Participatory action research to implement a model of collaboration between allopathic and traditional healthcare practitioners in the management of HIV/AIDS and TB - Ngunyulu, Roinah Nkhensani (University of Pretoria, 2024)
Thesis (PhD (Nursing Science))--University of Pretoria, 2024